Impacts on the CV parent body: A coordinated, multiscale fabric analysis of the Allende meteorite. (27th March 2023) - Forman, L. V.; Daly, L.; Bland, P. A.; Benedix, G. K.; Corrigan, C.
Abstract: Evidence of impact‐induced compaction in the carbonaceous chondrites, specifically CMs and CVs, has been widely investigated utilizing microscopy techniques and impact experiments. Here, we use high‐resolution photography and large area and high‐resolution electron backscattered diffraction (EBSD) mapping analyses in tandem, to explore the effects of impact‐induced compaction at both the meso‐ and micro‐scales in the Allende CV3.6 carbonaceous chondrite. Macro‐scale photography images of a ~25 cm slab of Allende captured meso‐scale features including calcium‐aluminum inclusions (CAIs) and chondrules. CAIs have a long‐axis shape‐preferred orientation (SPO). Examination of such meso‐scale features in thin section revealed the same trend. Matrix grains from this section display a large amount of heterogeneity in petrofabric orientation; microscale, high‐resolution, large area EBSD mapping of ~300, 000 olivine matrix grains; high‐resolution large area EBSD map across an elongate CAI; and a series of high‐resolution EBSD maps around two chondrules and around the CAI revealed crystallographic preferred orientations (CPOs) in different directions. Finally, internal grains of the CAI were found to demonstrate a weak lineation CPO, the first crystallographic detection of possible CAI "flow." All results are consistent with multiple, gentle impacts on the Allende parent body causing hemispheric compaction. The larger, more resistant components are likely to have been compressed and oriented by earlier impacts, and the matrix region petrofabrics and CAI "flow" likely occurred during subsequent impacts. Meteoritic components respond differently to impact events, and consequently, it is likely that different components would retain evidence of different impact events and angles.